2013
DOI: 10.1055/s-0032-1328402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Theoretical Study on the Anti-inflammatory Mechanism of 1-Nitro-2-phenylethane

Abstract: In this study, 1-nitro-2-phenylethane was evaluated with respect to its effects in edema models of acute inflammation induced with carrageenan, dextran, and croton oil. 1-Nitro-2-phenylethane produced inhibition of rat paw edema induced by carrageenan and dextran at the doses of 25 and 50 mg/kg. The same doses caused an inhibition of croton oil-induced ear edema in mice. Our results suggest that 1-nitro-2-phenylethane has anti-inflammatory activity, probably of peripheral origin, acting in the synthesis and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The screening proceeded also revealed that it modulates only peripheral components of nociception, despite apparently involving opioid receptors in its mechanism of action (Lima et al, 2009). In inflammatory context, the results indicate the reduction of edema induced by croton oil, carrageenan, and dextran, with oral doses of 25 and 50 mg/kg (Vale et al, 2013). A possible mechanism related to these effects was pointed out by a conformational study conducted by Vale et al (2013) who demonstrated that 1N2PE molecule had a favorable configuration for interaction with prostaglandin endoperoxide synthase.…”
Section: Antinociceptive and Anti-inflammatory Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…The screening proceeded also revealed that it modulates only peripheral components of nociception, despite apparently involving opioid receptors in its mechanism of action (Lima et al, 2009). In inflammatory context, the results indicate the reduction of edema induced by croton oil, carrageenan, and dextran, with oral doses of 25 and 50 mg/kg (Vale et al, 2013). A possible mechanism related to these effects was pointed out by a conformational study conducted by Vale et al (2013) who demonstrated that 1N2PE molecule had a favorable configuration for interaction with prostaglandin endoperoxide synthase.…”
Section: Antinociceptive and Anti-inflammatory Activitymentioning
confidence: 96%
“…In this context, A. canelilla has shown promise, since published studies have ratified, in murine models, its antinociceptive and anti-inflammatory properties referred in traditional use. The study initially conducted by Lima (2008), later expanded and published in two other articles (Lima et al, 2009;Vale et al, 2013), demonstrated antinociceptive and anti-inflammatory activity using a fraction of the AcEO containing 1N2PE with 97.5 to 99% purity. This product was therefore applied to classic models of antinociceptive activity (abdominal contortions, hot plaque, and formalin) and antiedematogency (croton oil ear edema, paw edema by carrageenan or dextran), in addition to performing a theoretical study of functional density calculations.…”
Section: Antinociceptive and Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…1-Nitro-2-phenylethane (NPH) is a volatile compound found in the EOs of Aniba canelilla and Dennettia tripetala [58], and was the first nitrocomponent isolated from plants [238,239]. Several pharmacological activities for NPH have been reported, including anti-inflammatory [240], antinociceptive [241], trypanocidal [242], cytoprotective [243], anxiolytic and hypnotic effects [58]. NPH also presents vasodilator activity via stimulation of soluble guanylil cyclase [244], and induces vagal-vagal bradycardia in normotensive rats [245].…”
Section: -Nitro-2-phenylethanementioning
confidence: 99%
“…NPE has been shown to exert antinociceptive [ 9 ] and, vasorelaxant [ 10 , 11 ] effects in vivo. Furthermore, a recent study has suggested that NPE also has anti-inflammatory activity, as demonstrated by its ability to inhibit paw edema induced by dextran and carrageenan in rats and by croton oil in mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%